Posterior reversible encephalopathy syndrome in stroke-prone spontaneously hypertensive rats on high-salt diet. Issue 7 (July 2019) - Herisson, Fanny; Zhou, Iris; Mawet, Jerome; Du, E; Barfejani, Arnavaz H; Qin, Tao; Cipolla, Marilyn J; Sun, Philip Z; Rost, Natalia S; Ayata, Cenk
Stroke-prone spontaneously hypertensive rats (SHRSP) on high-salt diet are characterized by extremely high arterial pressures, and have been endorsed as a model for hypertensive small vessel disease and vascular cognitive impairment. However, rapidly developing malignant hypertension is a well-known cause of posterior reversible encephalopathy syndrome (PRES) in humans, associated with acute neurological deficits, seizures, vasogenic cerebral edema and microhemorrhages. In this study, we aimed to examine the overlap between human PRES and SHRSP on high-salt diet. In SHRSP, arterial blood pressure progressively increased after the onset of high-salt diet and seizure-like signs emerged within three to five weeks. MRI revealed progressive T2-hyperintense lesions suggestive of vasogenic edema predominantly in the cortical watershed and white matter regions. Histopathology confirmed severe blood–brain barrier disruption, white matter vacuolization and microbleeds that were more severe posteriorly. Hematological data suggested a thrombotic microangiopathy as a potential underlying mechanism. Unilateral common carotid artery occlusion protected the ipsilateral hemisphere from neuropathological abnormalities. Notably, all MRI and histopathological abnormalities were acutely reversible upon switching to regular diet and starting antihypertensive treatment. Altogether our data suggest that SHRSP on high-salt diet recapitulates the neurological, histopathological and imaging features of human PRES rather than chronic progressive small vessel disease.